COLOR CHANGES OF 3D PRINTED AND CONVENTIONAL DENTAL RESINS FOR REMOVABLE PROSTHODONTICS AFTER IMMERSION IN DIFFERENT STAINING AGENTS - Mariya Dimitrova; Angelina Vlahova; Ilian Hristov; Rada Kazakova; Bozhana Chuchulska; Anastasia Gladysheva (Peytchinski Publishing, 2023)
Introduction: The discoloration of the denture base resins is one of the shortcomings of this type of dental materials, and it could be determined through various visual and instrumental methods. The aim of the current study was to evaluate the color stability of 3Dprinted and conventional denture base resins after immersion in different staining solutions. Materials and methods: A total of 200specimens were manufactured from two types of materials: 3D printed dental resin NextDent Denture 3D+ (NextDent, 3D Systems, The Netherlands) and heat-polymerized PMMA Vertex (3D Systems, The Netherlands), which were immersed in four types of colorants - artificial saliva, coffee, red wine and coke (n = 25). For measuring the color changes (CIE-L*a*b* system) of all specimens after storage in artificial saliva for 24 h at 37 degrees C (T0), a spectrophotometer SpectroShade Micro (SpectroShade, USA) was used. After seven days (T1), 14 days (T2) and 21 days (T3), the mean ∆E values were calculated and compared by Bonferonni post-hoc test. The data were processed using thestatistical software SPSS 26. The level of significance forrejecting the null hypothesis was fixed at p<0,05. Results: The values for ΔE were investigated, and the interactions between the type of material,the immersion time and the different staining solutions were statistically significant. The highest mean for ∆E was evaluated for both types of dental resin in red wine. Respectively, 3D printed specimens in artificial saliva were with the lowest mean. Conclusions: The 3D printed denture base resin demonstrated better color stability than the conventional acrylic materials. The staining effect correlated with the immersion time, with the red wine and coke being with the most chromogenic impact and the period with the highest color changes being 21 days.There was a significant interaction between theselected time periods and the type of staining agent, as both types of dental materials showedchanges in color stability at T1 compared to T3.